2018
DOI: 10.1111/1750-3841.14180
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the Antimicrobial Activity Research of Clove Oil and Eugenol in the Food Antisepsis Field

Abstract: As potential and valuable antiseptics in the food industry, clove oil and its main effective composition eugenol show beneficial advantages on antibacterial and antifungal activity, aromaticity, and safety. Researches find that both clove oil and eugenol express significantly inhibitory effects on numerous kinds of food source microorganisms, and the mechanisms are associated with reducing the migratory and adhesion and inhibiting the synthesis of biofilm and various virulence factors of these microorganisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 58 publications
2
61
0
1
Order By: Relevance
“…e inhibition halos induced by S. aromaticum essential oil were higher than eugenol standard. It has been reported that essential oil possesses antimicrobial activity due to the presence of eugenol, which is described as the most important component of cloves, but such activity has also been found to be due to other phenolic compounds [33,34]. Our results make it evident that the biocomplex is responsible for such activity, reinforcing the results of MIC determination.…”
Section: Discussionsupporting
confidence: 85%
“…e inhibition halos induced by S. aromaticum essential oil were higher than eugenol standard. It has been reported that essential oil possesses antimicrobial activity due to the presence of eugenol, which is described as the most important component of cloves, but such activity has also been found to be due to other phenolic compounds [33,34]. Our results make it evident that the biocomplex is responsible for such activity, reinforcing the results of MIC determination.…”
Section: Discussionsupporting
confidence: 85%
“…12,15 Among them, carvacrol (from oregano) and eugenol (from clove bud) are EOs used as antimicrobials. [16][17][18][19] The carvacrol in concentrations between 0.8 and 1.2 wt% presents a content of phenolic groups that acts directly in the cytoplasmic membrane responding against Gram-negative bacteria. 16,17 Eugenol in concentrations between 1 and 5 wt% acts effectively against Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol (Eug) is a botanical spice with a strong clove scent, and is often used as a food preservative (Hu, Zhou, & Wei, 2018;Zhang, Zhang, Xu, & Hu, 2017) and in food packaging (Garrido-Miranda, Rivas, Perez-Rivera, Sanfuentes, & Pena-Farfal, 2018) due to its antibacterial, antifungal, antioxidant and various properties (Prasad, 2013). The eugenol group of compounds include eugenol, isoeugenol, methyl eugenol, methyl isoeugenol, etc.…”
Section: Introductionmentioning
confidence: 99%